GARPU SERBU (GERAKAN PEDULI KELUARGA SEMUA IKUT MEMBANTU) SEBAGAI UPAYA PENCEGAHAN KOMPLIKASI KEHAMILAN RESIKO TINGGI - suparni, ita (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Abstract The pregnancy period requires special attention because it is an important period in the 1,000 days of life. Pregnant women are one of the groups that are vulnerable to nutrition. The nutritional intake of pregnant women greatly influences fetal growth. Based on data in Bangsongan Village up to September 2023, it was found that there were 40 pregnant women who were at high risk, and 18 pregnant women experienced malnutrition. The nutritional intake of pregnant women greatly influences fetal growth. The aim of this service activity is to reduce the maternal mortality rate and infant mortality rate by making home visits to monitor the health of pregnant women by involving cross-sectors in Bangsongan Village, Kayen Kidul District, Kediri Regency by holding the GARPU SERBU center program. Activities will be carried out on 5 - 16 September 2023 involving village midwives, nutrition teams, nurses, community health workers, health promotion and posyandu cadres. Activities are carried out by conducting home visits to high-risk pregnant women, carrying out environmental health checks, data collection on high-risk pregnant women, maternal health checks, taking water samples, education on Health of Maternal and Child, clean and healthy living behavioral, nutrition for pregnant women, as well as providing additional food to pregnant women. Evaluation of activity results was obtained from 40 high risk pregnant women, identified as 28 High Risk and 12 Very High Risk. Mothers understood the information and education provided by the team of Nutrition officers, and were willing to accept providing additional food for pregnant women with chronic lack of energy. With the Garpu Serbu Innovation, it is hoped that the achievement process that has been carried out can be achieved, as well as being able to make improvements to programs that have not been running well. It is hoped that this innovation will continue to be implemented by the village and midwives in collaboration with the Community Health Center.